2021
DOI: 10.1021/acs.inorgchem.1c02668
|View full text |Cite
|
Sign up to set email alerts
|

Elaboration on the Electronics of Salen Manganese Nitrides: Investigations into Alkoxy-Substituted Ligand Scaffolds

Abstract: The ligand electronics of salen manganese nitride complexes directly influence the locus of oxidation and, thus, the reactivity of the resulting oxidized species. This work investigates the influence of tert-butoxy, isopropoxy, and methoxy substituents on the electronics of salen manganese nitride species and includes the first documentation of the para Hammett value for the tert-butoxy substituent (σpara = −0.13 ± 0.03). Each alkoxy-substituted complex undergoes metal-based oxidation to form manganese­(VI), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…We have reported that oxidation of nitridomanganese­(V) salen complexes (“salen” being a common abbreviation for N 2 O 2 bis-phenolate bis-Schiff-base ligands) results in an electronic structure that can be tuned through the modulation of para -R phenolate substituents, without altering the geometry at the metal center. , Salen ligands exhibit redox-active behavior and have the potential to undergo oxidation (or reduction) at the ligand in place of the metal. We, and others, have observed that the formation of a Mn VI salen nitride upon oxidation results in an activated MnN bond that rapidly homocouples to form N 2 , even at a low temperature. ,, Interestingly, para -R substitution with electron-donating substituents (R = NMe 2 ) resulted in ligand radical formation where homocoupling was not observed, even at room temperature . Recent reports have utilized Mn salen nitrides to study the hydrogen atom bond dissociation free energy of the associated imido complexes, formation of ammonia via proton-coupled electron transfer, and as catalysts for ammonia oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that oxidation of nitridomanganese­(V) salen complexes (“salen” being a common abbreviation for N 2 O 2 bis-phenolate bis-Schiff-base ligands) results in an electronic structure that can be tuned through the modulation of para -R phenolate substituents, without altering the geometry at the metal center. , Salen ligands exhibit redox-active behavior and have the potential to undergo oxidation (or reduction) at the ligand in place of the metal. We, and others, have observed that the formation of a Mn VI salen nitride upon oxidation results in an activated MnN bond that rapidly homocouples to form N 2 , even at a low temperature. ,, Interestingly, para -R substitution with electron-donating substituents (R = NMe 2 ) resulted in ligand radical formation where homocoupling was not observed, even at room temperature . Recent reports have utilized Mn salen nitrides to study the hydrogen atom bond dissociation free energy of the associated imido complexes, formation of ammonia via proton-coupled electron transfer, and as catalysts for ammonia oxidation .…”
Section: Introductionmentioning
confidence: 99%
“…In accord with experimental data, calculations on the one-electron oxidized complexes predict a Mn VI electronic ground state for R = CF 3 , tBu, O i Pr, H, while a Mn V ligand radical ground state was predicted for R = NMe 2 , NEt 2 (vide supra). 62,63 We next evaluated the difference in nitride NPA charge between the neutral and oxidized forms, with the Mn VI derivatives exhibiting a much more signicant increase in nitride NPA charge and therefore electrophilicity upon oxidation in comparison to the Mn V ligand radical derivatives (Fig. 6).…”
Section: Theoretical Calculationsmentioning
confidence: 99%
“…Mn(Sal CF3 )N, Mn(Sal tBu )N, Mn(Sal OiPr )N and Mn(Sal NMe2 )N have been previously synthesized. 62,63 For the two new complexes, unsubstituted Mn(Sal H )N was prepared by the reaction of corresponding manganese chloride salt with NH 4 OH as reported by Carreira and coworkers (Scheme S1 and Fig. S1 †).…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the solution was frozen after 10 min at 70K, it showed an EPR spectrum with peaks at effective gvalues (g ≈ 2) (Scheme 4, (e)). The aminium radical-cation (g = 2.0028) and triplet Mn ligand radical was observed for the spectrum of EPR, 18 which was consistent with the hypothesis that Mn−N intermediates would exist in triplet electronic ground states. At last, aziridine product 9 was assessed with styrene and p-toluenesulfonamide, 16 which revealed that the reaction of (Salen)Mn(III)-catalyzed enantioselective intramolecular haloamination of alkenes could generate a chiral aziridines intermediate.…”
mentioning
confidence: 99%